2015
DOI: 10.1088/0029-5515/55/9/093004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of zonal flows by using the collective scattering measurement of density fluctuations

Abstract: The poloidal × E B r T rotation velocities in the core plasma region are studied using the instantaneous frequency method (IFM) with the density fluctuations measured by the CO 2 laser collective scattering diagnostics on the HT-7 tokamak. A coherent mode is observed in the fluctuations of poloidal velocities with the mode frequency from 10 to 20 kHz. It is identified as geodesic acoustic mode (GAM) zonal flow with poloidal symmetry (m = 0) and its mode frequency coinciding with the theoretical expected GAM fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Research on several tokamaks and stellerators in various plasma conditions has shown that the fluctuation velocity is often dominated by the E × B term [27][28][29][30][31]. But the hypothesis of negligible phase velocity is not completely trivial in some cases, especially in the confinement mode transition [25] and in Ohmic confinement with low injected torque [32,33].…”
Section: Experimental Techniques and Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on several tokamaks and stellerators in various plasma conditions has shown that the fluctuation velocity is often dominated by the E × B term [27][28][29][30][31]. But the hypothesis of negligible phase velocity is not completely trivial in some cases, especially in the confinement mode transition [25] and in Ohmic confinement with low injected torque [32,33].…”
Section: Experimental Techniques and Apparatusmentioning
confidence: 99%
“…where S k (t, f) is the spectrogram of turbulence at wave number k, and the integrated power of turbulence at k can be calculated by S k (t) = S k (t, f). Some research on poloidal velocity has already been carried out with the diagnostics during steady-state discharges [31,36].…”
Section: Experimental Techniques and Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Keen tools are important to diagnose turbulent parameters in wave-number domain. A conventional diagnostic is far-forward laser scattering [5,6]. But this diagnostic is not very suitable for low k circumstances, and the usage of this method is strongly limited by the inevitable refraction of the incident laser beam as the great improvement of plasma density in tokamaks.…”
Section: Introductionmentioning
confidence: 99%
“…The turbulent energy spectrum will show an exponential decay as the increasing of k, which means that we should investigate not only the turbulence with high k such as the electron temperature gradient mode [1] but also that with low k such as the ion temperature gradient mode [2] and trapped electron mode [3]. The far-forward laser scattering diagnostic [4][5][6] which can measure density fluctuations with high k, is not suitable for low k circumstances for the limited scattering angle. Phase contrast imaging (PCI) [7], which can diagnose long wavelength density fluctuations, is a keen tool to investigate the wide-spectrum characteristics and is developed in many magnetic confinement devices, such as DIII-D [8], Alcator C-Mod [9], LHD [10], TEXT-U [11].…”
Section: Introductionmentioning
confidence: 99%